Fault ride‐through strategy for hybrid HVDC with cascaded multi‐infeed MMC inverters - Jingbo Zhao (Wiley, 2021)
Abstract The hybrid HVDC with cascaded multi‐infeed MMC inverters suffers from the fragile characteristic of its MMC inverters and is easy to be over current and over voltage. To solve such a problem, this letter proposes a fault ride‐through strategy based on the fault current limiter with a novel topology. With the proposed limiter, the hybrid HVDC system can ride through both the DC side pole‐to‐ground fault and the commutation failure caused by the AC side fault. When the commutation failure happens, the current‐limiting resistor of the fault current limiter will be put on to decrease the current into the safety boundary. When the DC side pole‐to‐ground fault happens, the MMC capacitor discharge path will be cut off automatically by the topology of the fault current limiter. The simulations finally validate the analysis.